MOLECULAR AND PHYLOGENETIC ANALYSIS OF CRYPTOSPORIDIUM SPP. ISOLATED FROM CHILDREN, LAMBS AND GOAT KIDS. - Duha Faisal Enaad1 , Tareq Rifaaht Minnat2; Haleem Hamza Hussian3. (Chelonian Research Foundation, 2023)
To offer details on the infection rate of cryptosporidiosis in farmed small ruminants and the possibility of goat and lamb offspring acting as zoonotic reservoirs for the cryptosporidiosis virus in youngsters. 200 fecal samples from 100 children,65 lambs and 35 goat kids,were collected between September 2022 and May 2023 from various regions within the Diyala governorate. To check for Cryptosporidium spp. infection, traditional methods (Sheather's flotation technique and modified ziehl-neelsen staining microscopic examination) were employed. The total Cryptosporidium-positive isolates by conventional methods were (53/65) 81.5% in diarrheic cases of lambs, (15/35) 42.9% in goat kids and (21/100) 21% in children. Furthermore, forty Cryptosporidium-positive isolates were investigated utilizing subtyping and genotyping methods. Through sequencing of a selection of 20 isolates and restriction studies of PCR products from small-subunit 18s rRNA genes from microscopy-positive isolates, Cryptosporidium parvum and C. scrofarum were identified. The first application of phylogenetic analysis is to help resolve the controversy surrounding the taxonomy of the genus Cryptosporidium. Ten children, five lambs, and five children's genomes were used to create a phylogenetic tree that describes the 20 sequenced isolates of Cryptosporidium species. These results imply that a significant source of the zoonotic C. parvum and C. scrofarum for humans is goat offspring, specifically lambs. It was discovered that the disease mainly afflicted sheep and goats by comparing newly isolated strains of Cryptosporidium scrofarum from Iraq with previously documented cases. Key words: Molecular, Phylogenetic Analysis, Cryptosporidiosis, Lambs, Goat Kids, Children.